Sustainability of convergence in the context of macro-prudential policies in the European Union - Cristina Maria Triandafil (Romanian Academy, National Institute for Economic Research, 2013)
This postdoctoral research aimed to highlight sustainability convergence criteria in the context of financialisation, with impact on the prudential regulator. Based on complex analysis, the research work has revealed that countries in Central and Eastern Europe still face significant macroeconomic risks caused by fragile macroeconomic structures. These countries have been undergoing a catching up process that contributes to the amplification of divergence across the European Union. Being heavily dependent on external financial flows, these countries involve a high macro-prudential risk, affecting the pace of real convergence.
Keywords: E20; E60; E51; E52; 330; convergence; macro-prudential; sustenability; nominal and real economy